Zamia furfuracea Cardboard Plant, Cardboard Cycad - Edward Gilman (EDIS, 2007)
The publication provides detailed information about the cardboard plant, also known as Zamia furfuracea. This plant features rigid, woody, medium-green foliage that forms a loose, symmetrical rosette. It is well-suited for tropical landscapes, container planting, or as a specimen plant. The cardboard plant thrives in a variety of well-drained soils and can grow in both full sun and partial shade. It is highly drought-tolerant once established and has minimal pest issues, with Florida red scale being the primary concern. The publication also highlights the plant’s ornamental value, slow growth rate, and suitability for indoor cultivation. First published Oct. 1999.